A Soul of Truth in Things Erroneous: Popper S "Amateurish" Evolutionary Philosophy in Light of Contemporary Biology - Vecchi, D (Stazione Zoologica Anton Dohrn, 2015)
This paper will critically assess Popper s evolutionary philosophy. There exists a rich literature on the topic with which we have many reservations. We believe that Popper s evolutionary philosophy should be assessed in light of the intriguing theoretical insights offered, during the last 10 years or so, by the philosophy of biology, evolutionary biology and molecular biology. We will argue that, when analysed in this manner, Popper s ideas concerning the nature of selection, Lamarckism and the theoretical limits of neo-Darwinism can be appreciated in their full biological and philosophical value. © Springer International Publishing AG 2014.